Rancang Bangun Sistem Informasi Pembelian dan Penjualan Sparepart Motor di Bengkel Qira Moto - Nova Indrayana Yusman; Anggit Suryopratomo; Silva Alviyani; Agreindra Helmiawan (Ma'soem University, 2022)
The design and manufacture of an Information System for the Purchase and Sale of Motorcycle Parts is a system created to overcome the problems that occur, including minimizing the loss or damage of transaction evidence and making it easier to make transaction reports. The research method used is the SLDC (System Development Life Cycle) system and the waterfall model. System analysis and design tools used in this final project are Flowmap, DFD (Data Flow Diagram), ERD (Entity Relationship Diagram), Structure Chart, and Database Relationship Schema. The results achieved by making this information system are minimizing loss or damage to evidence of transactions, simplifying the process of controlling and searching for stock items and making it easier to make purchase and sale transaction reports.